2017
DOI: 10.1016/j.dcn.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive components underpinning the development of model-based learning

Abstract: Reinforcement learning theory distinguishes “model-free” learning, which fosters reflexive repetition of previously rewarded actions, from “model-based” learning, which recruits a mental model of the environment to flexibly select goal-directed actions. Whereas model-free learning is evident across development, recruitment of model-based learning appears to increase with age. However, the cognitive processes underlying the development of model-based learning remain poorly characterized. Here, we examined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 45 publications
8
51
4
Order By: Relevance
“…A substantial body of literature supports the notion that sign tracking and goal tracking are the behavioral outputs of two parallel reinforcement learning processes-akin to model-free and model-based learning, respectively (Clark et al, 2012;Huys et al, 2014). Although there has been limited investigation of model-free vs. model-based learning in adolescents, especially in animal models, the predominant view is that model-free learning is present throughout the lifespan, whereas modelbased learning emerges slowly and is not fully integrated into behavior until adulthood (Decker et al, 2016;Potter et al, 2017). Our finding that adolescent rats perform more goal tracking and less sign tracking-and that such goal tracking is truly goal-oriented behavior, based on its sensitivity to reward devaluation-complicates this view.…”
Section: Discussionmentioning
confidence: 84%
“…A substantial body of literature supports the notion that sign tracking and goal tracking are the behavioral outputs of two parallel reinforcement learning processes-akin to model-free and model-based learning, respectively (Clark et al, 2012;Huys et al, 2014). Although there has been limited investigation of model-free vs. model-based learning in adolescents, especially in animal models, the predominant view is that model-free learning is present throughout the lifespan, whereas modelbased learning emerges slowly and is not fully integrated into behavior until adulthood (Decker et al, 2016;Potter et al, 2017). Our finding that adolescent rats perform more goal tracking and less sign tracking-and that such goal tracking is truly goal-oriented behavior, based on its sensitivity to reward devaluation-complicates this view.…”
Section: Discussionmentioning
confidence: 84%
“…The use of WM to manipulate information may develop over adolescence ((Crone et al, 2006)), while the use of WM to maintain information perhaps develops earlier. Recent results with a simple WM assay, a verbal span task, found age groups aged 9 to 25 performed equally well ((Potter et al, 2017)) and thus found no developmental effects on WM. The lack of age effect on the WM capacity in our study may reflect the fact that WM is used to maintain stimulus-action associations, rather than to manipulate information.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we examined developmental changes in the working memory (WM) and reinforcement learning (RL) processes that contribute to simple stimulus-action association learning. While many developmental models emphasize late prefrontal cortex maturation and gains in WM in late adolescence ((Huizinga et al, 2006;Larsen & Luna, 2018)), previous studies have also shown changes in development in reinforcement learning tasks (Palminteri et al, 2016;Potter et al, 2017;Van Den Bos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations